Reversible control of magnetic domains in a Tb0.3Dy0.7Fe2/Pt/PbZr0.56Ti0.44O3 thin film heterostructure deposited on Pt/TiO2/SiO2/Si substrate - More-Chevalier, J.; Ferri, A.; Cibert, C.; Poullain, G.; Desfeux, R.; Bouregba, R. (Journal of applied physics, 2014)
Tb0.3Dy0.7Fe2/Pt/PbZr0.56Ti0.44O3 (Terfenol-D/Pt/PZT) magnetoelectric (ME) thin films were deposited on Pt/TiO2/SiO2/Si substrate. Ferroelectric and magnetic properties were characterized at room temperature. At zero dc magnetic field and out of mechanical resonance, a variation of the voltage across the ferroelectric film was obtained when a small external ac magnetic field was applied to the device. The corresponding ME voltage coefficient was 1.27 V/cm Oe. On the same sample, local magnetic domain patterns were imaged by magnetic force microscopy. Reversible changes in magnetic domain patterns were observed when a dc electric field of 120 to 360 kV/cm was applied to the ferroelectric layer. These results confirm that both magnetic control of ferroelectric polarization and electric control of magnetization are achievable on ME thin films devices deposited on silicon substrates.